(untitled) (Research, Society and Development, 2024)
Soybean cultivars present distinct agronomic performance depending on the production environment. The objective was to study the agronomic performance and adaptability of different soybean cultivars evaluated in the municipalities of Cândido Mota, Palmital and Brotas in order to identify the most suitable for planting in the helping producers and regional technicians in choosing the materials to be planted in the coming crops. The experimental design used was the one of completely randomized blocks, with 19 cultivars and 4 replications per trial, the means being grouped by using the Scott-Knott test at 5% probability. Information on adaptability and stability was determined by using the procedure of Annicchiarico (1992), modified by Schmildt et al. (2011). The traits evaluated were: plant height, first pod insertion height (AIPV), grain yield and thousand grain mass (MMG). It was found that there is a difference in grain yield, MMG, plant height and AIPV among the cultivars evaluated in different environments. There are commercial cultivars with broad adaptability (HO Paraguaçu, HO Iguaçu) and cultivars with specific adaptability (DM 66i68, NK 6356, NS 6446, GH 6433) depending on the production environment. Regional assessments must be carried out continuously and in different locations in order to obtain consistent information about the agronomic performance of new cultivars.